Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the problem of finding the velocity of the object at [tex]\( t = 2 \)[/tex] seconds given the acceleration function and initial velocity, we follow these steps:
1. Define the acceleration function [tex]\( a(t) \)[/tex]:
Given the acceleration function [tex]\( a(t) = (3t + 3)^{-4} \)[/tex].
2. Integrate the acceleration function to find the velocity function [tex]\( v(t) \)[/tex]:
To find the velocity function [tex]\( v(t) \)[/tex], we need to integrate the acceleration function with respect to time [tex]\( t \)[/tex]:
[tex]\[ v(t) = \int a(t) \, dt = \int (3t + 3)^{-4} \, dt \][/tex]
3. Perform the integration:
Integrate [tex]\( \int (3t + 3)^{-4} \, dt \)[/tex]. This can be done using integration techniques such as substitution.
Let [tex]\( u = 3t + 3 \)[/tex], hence [tex]\( du = 3 \, dt \)[/tex] or [tex]\( dt = \frac{du}{3} \)[/tex].
Substituting in, we get:
[tex]\[ \int (3t + 3)^{-4} \, dt = \int u^{-4} \, \frac{du}{3} = \frac{1}{3} \int u^{-4} \, du \][/tex]
The integral of [tex]\( u^{-4} \)[/tex] is:
[tex]\[ \int u^{-4} \, du = \frac{u^{-3}}{-3} = -\frac{1}{3} u^{-3} \][/tex]
Substituting back [tex]\( u = 3t + 3 \)[/tex]:
[tex]\[ -\frac{1}{3} \cdot \frac{1}{3(3t + 3)^3} = -\frac{1}{9(3t + 3)^3} \][/tex]
Therefore, the velocity function [tex]\( v(t) \)[/tex] is:
[tex]\[ v(t) = -\frac{1}{9(3t + 3)^3} + C \][/tex]
4. Determine the constant of integration [tex]\( C \)[/tex] using the initial condition:
Given that the velocity at [tex]\( t = 0 \)[/tex] is 4 meters per second:
[tex]\[ v(0) = 4 = -\frac{1}{9(3 \cdot 0 + 3)^3} + C = -\frac{1}{9 \cdot 27} + C = -\frac{1}{243} + C \][/tex]
Solving for [tex]\( C \)[/tex]:
[tex]\[ 4 = -\frac{1}{243} + C \implies C = 4 + \frac{1}{243} = \frac{972 + 1}{243} = \frac{973}{243} \][/tex]
Therefore, the function [tex]\( v(t) \)[/tex] becomes:
[tex]\[ v(t) = -\frac{1}{9(3t + 3)^3} + \frac{973}{243} \][/tex]
5. Calculate the velocity at [tex]\( t = 2 \)[/tex]:
Substitute [tex]\( t = 2 \)[/tex] into the velocity function:
[tex]\[ v(2) = -\frac{1}{9(3 \cdot 2 + 3)^3} + \frac{973}{243} = -\frac{1}{9 \cdot (6 + 3)^3} + \frac{973}{243} = -\frac{1}{9 \cdot 729} + \frac{973}{243} = -\frac{1}{6561} + \frac{973}{243} \][/tex]
Find a common denominator for these fractions:
[tex]\[ \frac{-1}{6561} + \frac{973 \cdot 27}{6561} = \frac{-1 + 26271}{6561} = \frac{26243}{6561} \][/tex]
6. Simplify and round to six decimal places:
Simplifying the fraction [tex]\(\frac{26243}{6561}\)[/tex] and converting to decimal form:
[tex]\[ v(2) \approx 3.999848 \][/tex]
Therefore, the velocity of the object 2 seconds later is approximately [tex]\(3.999848\)[/tex] meters per second.
1. Define the acceleration function [tex]\( a(t) \)[/tex]:
Given the acceleration function [tex]\( a(t) = (3t + 3)^{-4} \)[/tex].
2. Integrate the acceleration function to find the velocity function [tex]\( v(t) \)[/tex]:
To find the velocity function [tex]\( v(t) \)[/tex], we need to integrate the acceleration function with respect to time [tex]\( t \)[/tex]:
[tex]\[ v(t) = \int a(t) \, dt = \int (3t + 3)^{-4} \, dt \][/tex]
3. Perform the integration:
Integrate [tex]\( \int (3t + 3)^{-4} \, dt \)[/tex]. This can be done using integration techniques such as substitution.
Let [tex]\( u = 3t + 3 \)[/tex], hence [tex]\( du = 3 \, dt \)[/tex] or [tex]\( dt = \frac{du}{3} \)[/tex].
Substituting in, we get:
[tex]\[ \int (3t + 3)^{-4} \, dt = \int u^{-4} \, \frac{du}{3} = \frac{1}{3} \int u^{-4} \, du \][/tex]
The integral of [tex]\( u^{-4} \)[/tex] is:
[tex]\[ \int u^{-4} \, du = \frac{u^{-3}}{-3} = -\frac{1}{3} u^{-3} \][/tex]
Substituting back [tex]\( u = 3t + 3 \)[/tex]:
[tex]\[ -\frac{1}{3} \cdot \frac{1}{3(3t + 3)^3} = -\frac{1}{9(3t + 3)^3} \][/tex]
Therefore, the velocity function [tex]\( v(t) \)[/tex] is:
[tex]\[ v(t) = -\frac{1}{9(3t + 3)^3} + C \][/tex]
4. Determine the constant of integration [tex]\( C \)[/tex] using the initial condition:
Given that the velocity at [tex]\( t = 0 \)[/tex] is 4 meters per second:
[tex]\[ v(0) = 4 = -\frac{1}{9(3 \cdot 0 + 3)^3} + C = -\frac{1}{9 \cdot 27} + C = -\frac{1}{243} + C \][/tex]
Solving for [tex]\( C \)[/tex]:
[tex]\[ 4 = -\frac{1}{243} + C \implies C = 4 + \frac{1}{243} = \frac{972 + 1}{243} = \frac{973}{243} \][/tex]
Therefore, the function [tex]\( v(t) \)[/tex] becomes:
[tex]\[ v(t) = -\frac{1}{9(3t + 3)^3} + \frac{973}{243} \][/tex]
5. Calculate the velocity at [tex]\( t = 2 \)[/tex]:
Substitute [tex]\( t = 2 \)[/tex] into the velocity function:
[tex]\[ v(2) = -\frac{1}{9(3 \cdot 2 + 3)^3} + \frac{973}{243} = -\frac{1}{9 \cdot (6 + 3)^3} + \frac{973}{243} = -\frac{1}{9 \cdot 729} + \frac{973}{243} = -\frac{1}{6561} + \frac{973}{243} \][/tex]
Find a common denominator for these fractions:
[tex]\[ \frac{-1}{6561} + \frac{973 \cdot 27}{6561} = \frac{-1 + 26271}{6561} = \frac{26243}{6561} \][/tex]
6. Simplify and round to six decimal places:
Simplifying the fraction [tex]\(\frac{26243}{6561}\)[/tex] and converting to decimal form:
[tex]\[ v(2) \approx 3.999848 \][/tex]
Therefore, the velocity of the object 2 seconds later is approximately [tex]\(3.999848\)[/tex] meters per second.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.